2017
DOI: 10.1038/s41467-017-00422-w
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genomics of microglia implicates DLG4 (PSD95) in the white matter development of preterm infants

Abstract: Preterm birth places infants in an adverse environment that leads to abnormal brain development and cerebral injury through a poorly understood mechanism known to involve neuroinflammation. In this study, we integrate human and mouse molecular and neuroimaging data to investigate the role of microglia in preterm white matter damage. Using a mouse model where encephalopathy of prematurity is induced by systemic interleukin-1β administration, we undertake gene network analysis of the microglial transcriptomic re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
143
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 77 publications
(157 citation statements)
references
References 81 publications
(104 reference statements)
11
143
3
Order By: Relevance
“…We analyzed the isolated microglia for gene expression of markers associated with functional phenotypes including cytotoxic ( Nos2 , Ptgs2 , Cd32 ), repair and regeneration ( Arg1 , Lga3 , Igf1 ), and immunomodulatory ( Il1ra , Il4a , Socs3 ) phenotypes. Exposure to neuroinflammatory‐stimuli affected the gene expression as expected (Krishnan et al, ), with increased expression of all of the genes except for the gene for IGF1, which was decreased. IGF1 is a pleotropic growth factor necessary for myelonogenesis and known to be decreased by pro‐inflammatory microglial activation (Wlodarczyk et al, ).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…We analyzed the isolated microglia for gene expression of markers associated with functional phenotypes including cytotoxic ( Nos2 , Ptgs2 , Cd32 ), repair and regeneration ( Arg1 , Lga3 , Igf1 ), and immunomodulatory ( Il1ra , Il4a , Socs3 ) phenotypes. Exposure to neuroinflammatory‐stimuli affected the gene expression as expected (Krishnan et al, ), with increased expression of all of the genes except for the gene for IGF1, which was decreased. IGF1 is a pleotropic growth factor necessary for myelonogenesis and known to be decreased by pro‐inflammatory microglial activation (Wlodarczyk et al, ).…”
Section: Resultssupporting
confidence: 69%
“…We used a well‐characterized paradigm of systemic inflammation driven neuroinflammation (Favrais et al, ; Krishnan et al, ; Van Steenwinckel et al, ), which is known to have effects on brain development and behavior consistent with those reported in infants and children born preterm (Ball et al, ; Raju, Buist, Blaisdell, Moxey‐Mims, & Saigal, ). Experimental protocols were approved by the institutional guidelines of the Institute National de la Santé et de la Recherche Scientifique (Inserm) France.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous works have been published in the literature that have improved our understanding of the perinatal brain (Ball et al, 2013b(Ball et al, , 2017Counsell et al, 2013;Doria et al, 2010;Kapellou et al, 2006;Keunen et al, 2017;Krishnan et al, 2017;Xue et al, 2007;Dubois et al, 2008a,b;Pienaar et al, 2008;RodriguezCarranza et al, 2008;Awate et al, 2010;Hill et al, 2010;Rathbone et al, 2011;Moeskops et al, 2013;Li et al, 2014b,a;Meng et al, 2014;Nie et al, 2014;Wang et al, 2014;Engelhardt et al, 2015;Lefevre et al, 2015;Li et al, 2015b;Moeskops et al, 2015;Li et al, 2016;Hazlett et al, 2017). Study- ing the developing connectome will open up many opportunities in future, not least because neonatal brain imaging data is changing rapidly, at scales that can be clearly resolved using current MRI technology.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has also recently been reported that the common variant rs17203281 in DLG4 (also known as PSD95 , which encodes postsynaptic density protein 95) is associated with significant differences white-matter microstructure (as indexed by FA) in preterm infants. In addition to being a marker of post-synaptic density, DLG4 is also expressed by microglia, and the authors speculate that the rs17203281 variant could affect responses to neuroinflammation in children who are born preterm 161 .…”
Section: Influences Of Genes and Environmentmentioning
confidence: 99%